Red blood cell distribution width is an independent predictor of mortality following amputation for diabetic foot - Yeo Kwon Yoon; Jae Han Park; Hang Hwan Cho; Dong Woo Shim; Wonwoo Lee; Seung Hwan Han; Jin Woo Lee; Kwang Hwan Park (Scientific Reports)
Abstract Red blood cell distribution width (RDW) is a prognostic factor in various disorders. This study aimed to assess the prognostic value of RDW in patients undergoing amputation for diabetic foot. We retrospectively analyzed data on 415 patients who underwent diabetic foot amputation between January 2009 and January 2019. After establishing an optimal cutoff value of preoperative RDW for all-cause mortality, univariable and multivariable analyses with Cox proportional hazard model for survivorship and logistic regression analysis for prolonged hospital length of stay (> 30 days) were performed to identify significant prognostic factors. A preoperative RDW of 14.5% was the optimal cutoff value for predicting all-cause mortality. RDW ≥ 14.5% was significantly associated with increased all-cause mortality (hazard ratio, 2.55; 95% confidence interval [CI], 1.55–4.19; P < 0.001) on multivariable Cox proportional model analysis. Preoperative RDW ≥ 14.5% was also associated with a prolonged hospital length of stay after surgery (odds ratio, 2.17; 95% CI, 1.29–3.66; P = 0.004). Higher preoperative RDW was an independent predictive factor for increased all-cause mortality and prolonged hospital length of stay after diabetic foot amputation. These results suggest that RDW may be a useful laboratory parameter for risk stratification in patients undergoing amputation for diabetic foot.